Wear rate of epoxy resin reinforced with multi walls carbon nanotubes - Hameed, Ayad Qabash (Iraqi Journal of Physics, 2019)
In this study, nanocomposites have been prepared by addingmultiwall carbon nanotubes (MWCNTs) with weight ratios (0, 2, 3,4, 5) wt% to epoxy resin. The samples were prepared by hand lay-upmethod. Influence of an applied load before and after immersion insodium hydroxide (NaOH) of normality (0.3N) for (15 days) atlaboratory temperature on wear rate of Ep/MWCNTsnanocomposites was studied. The results showed that wear rateincreases with increasing the applied load for the as prepared andimmersed samples and after immersion. It was also found that epoxyresin reinforced with MWCNTs has wear rate less than neat epoxy.The sample (Ep + 5wt% of MWCNTs) has lower wear rate. Theimmersion effect in base solution led to increase in wear rate valuesfor all samples compared to natural condition.